ANALISIS LITERATUR TENTANG PEMANFAATAN MEDIA DIGITAL BAMBOOZLE TERHADAP PEMAHAMAN KONSEP SISWA DALAM PEMBELAJARAN PJOK MATERI KEBUGARAN JASMANI - Salsabila Fadilah; Hakim, Abdul; Ayu Febrianti, Fitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article examines the use of the digital media platform Bamboozle in Physical Education, Sports, and Health (PJOK) learning at the elementary school level. The purpose of this study is to analyze how utilizing the Bamboozle platform can enhance students' conceptual understanding and learning outcomes, particularly in the topic of physical fitness activities. This study specifically aims to investigate the impact of Bamboozle digital media on improving students' conceptual understanding of physical fitness activities. The method employed is a literature review, synthesizing relevant national and international research on game-based learning media and technology integration in PJOK instruction. Data sources were drawn from indexed journal articles published within the last ten years. The synthesis results indicate that game-based digital media, including Bamboozle, consistently contribute to increased learning motivation, student engagement, and learning outcomes compared to conventional methods. These findings underscore the importance of integrating interactive digital media into PJOK to create more effective, varied learning experiences tailored to the characteristics of elementary school students in the digital era. Thus, it can be concluded that the use of Bamboozle digital media has a positive and significant effect on students' conceptual understanding in PJOK learning. Keywords: PJOK, digital media, Bamboozle, literature review, learning motivation.